A dama e o unicórnio: uma leitura iconográfica - Pelosi, Solange Maria Leão [UNESP]; Salzedas, Nelyse Apparecida Melro [UNESP] (My University, 2012)
This paper embraces the tapestry, from Cluny Museum: La Dame a la Licorne. There are in two types of analyses: One is a diachronic vew and also a sincrhonic, which guide its pratice. In the tapestry La Dame a la Licorne at the Cluny Museum a reading based over the myths and symbols was the main line. \The first analyses, diachronic covers the temporality of the tapestry production, the second one, synchronic, describes the level of history, religion and myths envolved. This work consists in a process of actualization and an effort to bring closely the discussion over tapestry, using methods applied to non-verbal readings.
Keywords: Lady and unicorn tapestry; Iconographic